2012
DOI: 10.1136/bjophthalmol-2012-302089
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced depth imaging optical coherence tomography in long-standing Vogt–Koyanagi–Harada disease

Abstract: Patients with VKH and long-standing disease had thinner choroids when compared to controls. Progressive choroidal thinning related to disease duration was observed at the macula of these patients. Whether this finding is part of the natural history of the disease or the result of a clinically undetected choroidal inflammation remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
1
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 25 publications
3
46
1
10
Order By: Relevance
“…Our result suggests that SFCT may also be used to monitor disease activity in chronic VKH. However, SFCT is also negatively correlated with age and duration of disease, which is consistent with other studies 26 27. In this retrospective study, there was wide variation in the baseline duration of disease and SFCT.…”
Section: Discussionsupporting
confidence: 92%
“…Our result suggests that SFCT may also be used to monitor disease activity in chronic VKH. However, SFCT is also negatively correlated with age and duration of disease, which is consistent with other studies 26 27. In this retrospective study, there was wide variation in the baseline duration of disease and SFCT.…”
Section: Discussionsupporting
confidence: 92%
“…The CT in myopia also has a positive correlation with final visual acuity. 21,22 In polypoidal choroidal vasculopathy, 23 Vogt-Koyanagi-Harada disease, 24 and Behçet's disease, 25 the choroid is thickened during the active phase and thereafter shows progressive thinning. The CT, therefore, has the potential to be used as a parameter to monitor the activity of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have recently reported choroidal findings such as changes in the choroidal thickness or loss of the choriocapillaris in patients with VKH disease by utilizing enhanced depth imaging, spectral-domain opti-DOI: 10.1159/000481863 cal coherence tomography (SD-OCT), or swept-source optical coherence tomography [7][8][9][10][11]. However, a few retrospective studies have reported retinal findings such as changes in the inner retinal thickness in patients with VKH disease by using enhanced SD-OCT and have identified a correlation between the retinal pigment epithelium undulation index and changes in the retinal thickness in eyes with VKH disease [12,13].…”
Section: Introductionmentioning
confidence: 99%